Strategi Komunikasi untuk Meningkatkan Kesadaran Masyarakat dalam Membayar Zakat Maal - Asep Sudarman (Communicatus: Jurnal Ilmu komunikasi, 2018)
Poverty is a very serious problem faced by the Indonesian people and to immediately find and find solutions to reduce a problem in poverty. Zakat is one way to reduce poverty, by utilizing the zakat funds. Zakat Collector Unit (UPZ) in Rancasari Sub-District, Bandung City, is devoted to zakat management activities in conveying messages so that the public is aware of the importance of paying zakat mal if it is bishab and haul. So that a number of questions were formulated in the study: 1) What is the Communication Strategy in Planning? 2) What is the Communication Strategy in Implementation? 3) What is the Communication Strategy in Evaluation? The theory used in this study is a management approach communication strategy from Fred R. David which reveals that the strategy management process has three stages: Planning, Implementation and Evaluation. This theory is also strengthened by the communication strategy of Richard West Lynn H. Tunner with internal and external communication approaches. The method used in this study is observation, in-depth interviews and documentation. The results of this study: Planning both internally and externally is supported by the role of the chairman who carries out organizational command by optimizing existing fields. Implementation of the Zakat Collection Unit in Rancasari Subdistrict is still on activities outside zakat mall. Trust in the Zakat Collection Unit is still lacking. Socialization activities are still at the level of verbal delivery in certain groups or forums.Kemiskinan merupakan masalah yang sangat serius yang dihadapi oleh bangsa Indonesia dan untuk segera mencari dan menemukan solusi untuk mengurangi suatu persoalan dalam kemiskinan tersebut. Zakat merupakan salah satu cara untuk menekan angka kemiskinan, dengan memanfaatkan dana zakat tersebut. Unit Pengumpul Zakat (UPZ) Kecamatan Rancasari Kota Bandung pada kegiatan pengelolaan zakat maal dikhususkan dalam menyampaikan pesan agar masyarakat menyadari pentingnya membayar zakat mal bila sudah bishab dan haul. Sehingga dirumuskan beberapa pertanyaan dalam penelitian: 1) Bagaimana Strategi Komunikasi dalam Perencanaan? 2) Bagaimana Strategi Komunikasi dalam Implementasi? 3) Bagaimana Strategi Komunikasi dalam Evaluasi? Teori yang digunakan dalam penelitian ini adalah strategi komunikasi pendekatan manajemen dari Fred R. David yang mengungkapkan bahawa proses manajemen strategi ada tiga tahapan yakni: Perencanaan, Implementasi dan Evaluasi. Teori ini juga dikuatkan oleh strategi komunikasi dari Richard West Lynn H. Tunner dengan pendekatan komunikasi internal dan eksternal. Metode yang digunakan dalam penelitian ini dalah observasi, wawancara mendalam dan dokumentasi.  Hasil dari penelitian ini: Perencanaan baik secara internal dan eksternal didukung oleh peran ketua yang menjalankan komando organisasi dengan mengoptimalkan bidang-bidang yang ada. Pelaksanaan implementasi Unit Pengumpul Zakat Kecamatan Rancasari masih pada kegiatan diluar zakat mal. Kepercayaan kepada Unit Pengumpul Zakat masih kurang. Kegiatan sosialisasi pun masih pada tataran penyampaian secara verbal pada kumpulan atau forum tertentu.